DINAMIKA ILMU KOMUNIKASI, CITIZENSHIP DAN PUBLIC SPHERE DALAM SATU DASAWARSA PASCA REZIM ORDE BARU: UPAYA PENGEMBANGAN SUB-KAJIAN KEBIJAKAN KOMUNIKASI DAN DEMOKRASI - Nyarwi Nyarwi (Jurnal Ilmu Komunikasi, 2008)
The contribution of communication studies in citizenship is the main issue in this paper, especially communication praxis in public sphere. In this context, the contrtibution of commu- nication studies in democratitation and politics discourse in the decade after new order needs to be reflected. There are many phenomena after the new order rezim, included interaction, contes- tation, negotiation, and structuration in public sphere which is not enough interest in communi- cation studies. The exsistance of public sphere is not only dominated by the state apparatus, moreover by Ideological apparatus, Market Apparatus or Ideological Market Apparatus. The communication determination in public sphere and citizenship discourse is the interesting topics to discuss.